Entre fé e liberdade: catolicismo, operariado e ditadura no ABC paulista (1964-1985) - Damião Sobrinho, Felipe Cosme (2015)
The following text is a Theology master's degree about the relation between the Catholic Church and the Society in ABC Region from 1964 to 1985. The objetive of the research is to improve the church's action towards the social challenges in the region that precedes and comes upon the Second Vatican Council where the eclesiological conception approaches the catholicism in the contemporary world. The militar civil coup caused by unstable politics and the need of structural reform in the country during this period. The Catholic Church presence in Bishop Jorge Marcos de Oliveira and Bishop Cláudio Hummes's pastoral action, both of them were diocesan bishops of Santo André in the period and contributed to the reflection about the interpretation of the relations between temporal and spiritual power in an institucional transformation period. The conception of revolution developed by Hannah Arendt will help with the dissertation verification of main hypothesis, examining the conception of mission of the catholic religion in the ABC region in social transformation (working class moviment and dictatorial governement) and with their own identity formation